The constitutional principles of the state’s political system as determining the foundations of electoral law: - Stępień-Załucka, Beata; Uliasz, Joanna (The Opole Studies in Administration and Law, 2024)
The political systems of democratic states are based on specific assumptions contained in the highest legal acts. In Poland, the role of the highest legal act is fulfilled by the Constitution of the Republic of Poland, and these assumptions are constitutional principles. Their uniform definition has been worked out neither by the legal system nor by the doctrine (Masternak-Kubiak 2003:142 and n.) Hence, they are sometimes defined differently in science. While for some they are "statements of the legislator of fundamental importance for the functioning of the constitutional system of the state" (Prokop 2014: 73), for others they are instruments of law from which certain norms are derived and thus influence the shaping of the principles of the political system or the administration of justice regardless of whether they are of a primary or secondary nature (Jarosz and Zawadzki 1980: 104-105). B. Banaszak emphasises that within individual constitutional norms it is possible to indicate principles of particular importance both for the state (Banaszak and Artur Preisner 1993). And what is more, the indication of a particular principle at the beginning of the constitution or in a part of it has consequences on its further provisions (Banaszak 1999: 18). W. J. Wołpiuk, in turn, writes that in a descriptive sense, principles are a certain pattern for research purposes (Wołpiuk. and Kuciński 2012: 94). A. Kallas, on the other hand, defines constitutional principles as principles fundamental to the nature of the state (Kallas 2007:121). These principles take the form of separate (individual) provisions, included in the body of Chapter I of the constitution, but are often also constructed on the basis of a number of its provisions (e.g. the principle of parliamentary system of government). Already worth noting at this point, however, is a certain regularity that in the constitutions of the former communist states of Central and Eastern Europe, they are as a rule quite extensive (Masternak-Kubiak 2003: 142 and n.). and have a broad spectrum of impact on the entire legal system. This spectrum is particularly relevant in electoral law. This article will therefore examine this spectrum. This is because it will show the impact of constitutional principles such as the principle of a republican state, the principle of the sovereignty of the nation, the principle of representation, the principle of political pluralism and the openness of political party financing on the basic premises of electoral law in terms of its subject and subject matter. While the key thesis to be proven is that the consequence of the above-mentioned constitutional principles is, inter alia, the tenure of the supreme organs of the state (including the Sejm and the Senate as representative bodies), renewable of their tenure, the universality of elections, the equality of elections and the secrecy of voting. The basic research methods used in the study will be dogmatic-legal and theoretical-legal method.